Psychological wellbeing of female refugees at Tongogara Refugee Camp. - Majoni, Annie Faith (Midlands State University, 2020)
Female refugees have been presented by many scholars as vulnerable to psychosocial problems during their journey to exile and upon resettlement where they would have sought sanctuary. The researcher is intrigued to employ a different perspective by researching on positive aspects of female refugees optimal functioning and their coping strategies amidst risk and protective factors to their psychological wellbeing. Psychological wellbeing will take an eclectic and ecological perspective in researching about refugees as a minority group. More so, the construct to be measured and assessed will borrow concepts and aspects of different fields of psychology. The researcher used a case study of randomly stratified sample of sixty (60) female refugees and purposively sampled thirty (30) female refugees at Tongogara Refugee Camp in Zimbabwe. The transformative paradigm is used to quantify the nature of female refugees’ psychological wellbeing using Ryff’s 42-version psychological wellbeing scale whilst a semi-structured interview qualifies the risk factors, protective factors and coping mechanisms of female refugees in the camp. Collected data is presented using charts and graphs while descriptive statistical and thematic analysis are employed. The results from the participants reveal that female refugees at Tongogara Refugee Camp have poor psychological wellbeing. Protective factors to the psychological wellbeing of female refugees in the camp included, social capital, social support systems, vocational training, and entrepreneurship. The risk factors that women face in the camp were financial and environmental insecurities, patriarchy, sexual and gender based violence (SGBV), poverty, stigma and discrimination, lack of legal recommendation and documentation, re-traumatization and pessimism. The researcher recommends participatory approaches to interventions given to refugees, legal recognition, educate them using their vernacular language as the language of instruction, empower women through protection from competent law enforcement agencies and for researchers to carry out studies on male refugees and employees working with female refugees. Most importantly researcher recommends the camp administrator to work with professional boards of psychology such that psychological services given to female refugees and employees working directly with them will not be done by paraprofessionals but with competent psychologists.